2020
DOI: 10.7554/elife.59770
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-satellite RNA transcripts are repressed by centromere–nucleolus associations

Abstract: Although originally thought to be silent chromosomal regions, centromeres are instead actively transcribed. However, the behavior and contributions of centromere-derived RNAs have remained unclear. Here, we used single-molecule fluorescence in-situ hybridization (smFISH) to detect alpha-satellite RNA transcripts in intact human cells. We find that alpha-satellite RNA-smFISH foci levels vary across cell lines and over the cell cycle, but do not remain associated with centromeres, displaying localization consist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 66 publications
6
55
0
Order By: Relevance
“…Accordingly, the amounts of the tested centromeric transcripts were also increased (Fig. 4 D), which is consistent with a recent report showing that CENP-B knockout increased centromeric RNA Fluorescence In Situ Hybridization signals (Bury et al, 2020). We next examined if CENP-B knockdown could strengthen centromeric cohesion.…”
Section: Cenp-b Knockdown Increases Centromeric Transcription and Strsupporting
confidence: 90%
See 1 more Smart Citation
“…Accordingly, the amounts of the tested centromeric transcripts were also increased (Fig. 4 D), which is consistent with a recent report showing that CENP-B knockout increased centromeric RNA Fluorescence In Situ Hybridization signals (Bury et al, 2020). We next examined if CENP-B knockdown could strengthen centromeric cohesion.…”
Section: Cenp-b Knockdown Increases Centromeric Transcription and Strsupporting
confidence: 90%
“…As treatment of transcriptional inhibitors for a few hours dramatically decreased the ongoing centromeric transcription but seemed not to do so for total RNAs, we believe that actively ongoing transcription rather than RNA transcripts plays a more important role in maintaining centromeric cohesion. This might explain why RPE-1 cells still exhibit strong centromeric cohesion even though they have a low amount of total centromeric RNA transcripts (Bury et al, 2020). Our findings here also suggest that increased centromeric transcription overall strengthens centromeric cohesion.…”
Section: Targeting Of the Transcriptional Suppressor Kox-1 With Cenp-supporting
confidence: 57%
“…Similarly, in mice, forced accumulation of the centromeric minor satellite transcripts leads to defects in chromosome segregation ( Bouzinba-Segard et al, 2006 ), while in human cells, the inhibition of the RNA polymerase II during mitosis leads to a decrease in centromeric α satellite transcription, anaphase lagging cells and abnormal chromosome splitting ( Chan et al, 2012 ; McNulty et al, 2017 ). This suggests that, in mammals, the transcription at the centromere is tightly regulated, maybe by its interaction with the nucleolus that may induce its repression ( Bury et al, 2020 ). In human cells, one of the regulators of cenRNA transcription is ZFAT, which binds to a specific DNA sequence present on each centromere ( Ishikura et al, 2020 ).…”
Section: Transcription At the Centromerementioning
confidence: 99%
“…More recently, a study found that human centromeric RNAs appear as multiple foci, which do not associate with centromeres. [26] The levels of these RNA foci vary over the cell cycle and across cell lines. However, the biochemical nature of these α-satellite RNA foci and their functions remain to be addressed.…”
Section: Functions Of Centromeric Rna Transcriptsmentioning
confidence: 99%